Layered and integrated medical countermeasures against Burkholderia pseudomallei infections in C57BL/6 mice - Klimko, Christopher P.; Shoe, Jennifer L.; Rill, Nathaniel O.; Hunter, Melissa; Dankmeyer, Jennifer L.; Talyansky, Yuli; Schmidt, Lindsey K.; Orne, Caitlyn E.; Fetterer, David P.; Biryukov, Sergei S.; Burtnick, Mary N.; Brett, Paul J.; et al. (Frontiers in Microbiology, 2022)
Burkholderia pseudomallei, the gram-negative bacterium that causes melioidosis, is notoriously difficult to treat with antibiotics. A significant effort has focused on identifying protective vaccine strategies to prevent melioidosis. However, when used as individual medical countermeasures both antibiotic treatments (therapeutics or post-exposure prophylaxes) and vaccine strategies remain suboptimal. Here we demonstrate that when used in combination, current vaccine strategies (recombinant protein subunits AhpC and/or Hcp1 plus capsular polysaccharide conjugated to CRM197 or the live attenuated vaccine strain 668 ∆ilvI) and co-trimoxazole regimens can result in near uniform protection in a mouse model of melioidosis due to apparent synergy associated with distinct medical counter-measures. These results were similar when examining several sub-optimal antibiotic regimens (e.g. seven day antibiotic course started early after infection or 21 day antibiotic course with delayed initiation). Importantly, this combinatorial strategy worked similarly when either protein subunit or live attenuated vaccines were evaluated. Layered and integrated medical countermeasures will provide novel treatment options for melioidosis as well as diseases caused by other bacterial pathogens that are refractory to individual strategies, particularly in the case of engineered or emerging bacterial biothreat agents.